STRATEGI PROMOSI MENINGKATKAN SALES DAN BRAND AWARENESS UKM X TERHADAP MINAT BELI KONSUMEN PADA MEDIA SOSIAL TIKTOK SHOP - Osel, Jefferson (Universitas Widya Kartika Surabaya, 2024)
The development of the times from year to year affects daily life and activities. This development has triggered the use of gadgets by using social media as a daily activity, including in the business sector. In this article entitled